Self-Efficacy toward Educational Technology : The Application in Taiwan Teacher Education - Wanyu Chao (Jiàoyù zīliào yǔ túshūguǎn xué, 2003)
In the twenty-first century, the rapid growth of information technologies has transformed the capacity of educational institutes to deliver educational and training programs.New technologies provide public accessibility to a vast variety of educational resources and learning opportunities. Technology integration in education can enhance learning and teaching. The quality of teaching, learning, researching, and course offerings must be considered in Taiwan teacher education. The learner s selfefficacy could undermine a valuable program if not recognized and dealt with in advance. The overall purpose of this paper is to discuss the application of self-efficacy in Taiwan teacher education. It should be considered and planned for before initiating programs to avoid potential roadblocks and to maximize returns in Taiwan teacher education toward computer technology.